2020
DOI: 10.1186/s13613-020-00782-5
|View full text |Cite
|
Sign up to set email alerts
|

Reliability and limits of transport-ventilators to safely ventilate severe patients in special surge situations

Abstract: Background Intensive Care Units (ICU) have sometimes been overwhelmed by the surge of COVID-19 patients. Extending ICU capacity can be limited by the lack of air and oxygen pressure sources available. Transport ventilators requiring only one O2 source may be used in such places. Objective To evaluate the performances of four transport ventilators and an ICU ventilator in simulated severe respiratory conditions. Materi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 20 publications
1
10
0
2
Order By: Relevance
“…We found that the Osiris3 performed worse than any other ventilator. In a previous bench study, this ventilator over-delivered V T at F I O 2 70%, as in the present study, but matched the target V T at 100%F I O 2 , 6 suggesting that the Venturi system was not optimal. Another bench study found that the Osiris3 tended to under-deliver V T , especially in case of airway obstruction.…”
Section: Editorsupporting
confidence: 54%
“…We found that the Osiris3 performed worse than any other ventilator. In a previous bench study, this ventilator over-delivered V T at F I O 2 70%, as in the present study, but matched the target V T at 100%F I O 2 , 6 suggesting that the Venturi system was not optimal. Another bench study found that the Osiris3 tended to under-deliver V T , especially in case of airway obstruction.…”
Section: Editorsupporting
confidence: 54%
“…L'Her et al classified emergency and transport ventilators according to their performances and technical reliability, even ergonomics: whereas Monnal T75 ® (Air Liquide Healthcare) was classified as "ICU-like emergency and transport-ventilators", Monnal T60 ® (Air Liquide Healthcare) and Elisée 350 ® (ResMed) were classified as "sophistical emergency and transport ventilators" [17,18]. In assist-control mode, three of the four tested transport ventilators both accurately controlled the volume delivered and had acceptable trigger delays in a recent bench study (Michigan test lung); two of the three were the Monnal T60 ® and Elisée 350 ® used in our transient ICUs [51]. Despite these bench tests results, using transport ventilators for ARDS management had never been achieved so far in clinical management for such a large number of patients who required a long invasive MV time.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, it is not possible to precisely titrate FiO 2 on a point-by-point basis but only to adjust per five percent increase or decrease. In addition, adjustments and monitoring of the I/E ratio are different from, and far less precise than, those for an ICU ventilator [20]. At the end of March 2020, the French government had to choose between two options: either organize the transfer of ICU workers from empty regions to overcrowded regions, or transfer patients already in ICUs.…”
Section: The Necessity To Help Overcrowded Areasmentioning
confidence: 99%